Three‐dimensional surface deformation derived from airborne interferometric UAVSAR: Application to the Slumgullion Landslide. Issue 5 (21st May 2016) - Delbridge, Brent G.; Bürgmann, Roland; Fielding, Eric; Hensley, Scott; Schulz, William H.
Abstract: In order to provide surface geodetic measurements with "landslide‐wide" spatial coverage, we develop and validate a method for the characterization of 3‐D surface deformation using the unique capabilities of the Uninhabited Aerial Vehicle Synthetic Aperture Radar (UAVSAR) airborne repeat‐pass radar interferometry system. We apply our method at the well‐studied Slumgullion Landslide, which is 3.9 km long and moves persistently at rates up to ∼2 cm/day. A comparison with concurrent GPS measurements validates this method and shows that it provides reliable and accurate 3‐D surface deformation measurements. The UAVSAR‐derived vector velocity field measurements accurately capture the sharp boundaries defining previously identified kinematic units and geomorphic domains within the landslide. We acquired data across the landslide during spring and summer and identify that the landslide moves more slowly during summer except at its head, presumably in response to spatiotemporal variations in snowmelt infiltration. In order to constrain the mechanics controlling landslide motion from surface velocity measurements, we present an inversion framework for the extraction of slide thickness and basal geometry from dense 3‐D surface velocity fields. We find that the average depth of the Slumgullion Landslide is 7.5 m, several meters less than previous depth estimates. We show that by considering a viscoplastic rheology, we can derive tighter theoretical bounds on the rheological parameter relating mean horizontal flow rate to surface velocity. Using inclinometer data for slow‐moving, clay‐rich landslides across the globe, we find a consistent value for the rheological parameter of 0.85 ± 0.08. Key Points: Provides reliable and accurate measurements of 3‐D surface deformation Inversion procedure to invert for landslide depth from 3‐D surface velocity measurements Viscoplastic flow provides tighter theoretical constraints on the rheological parameter